Roman influence on pottery from the ancient town Syene (Upper Egypt) - Rembart, Laura (Rei Cretariae Romanae Fautorum Acta, 2015)
Syene, the modern town Aswan, held an important significance in ancient times. The southernmost town of the Roman Empire, located at the first cataract, was an economic and political centre and made an important link between Egypt and the adjacent Nubia. Syene became the crossroads for the trade with goods from and to Inner Africa, including luxury goods like gold and ivory. Furthermore the town was the starting point for huge expeditions to Nubia. The red granite extracted in local quarries since Pharaonic times was another important export product of the region. It was shipped through the river ports of Syene and Elephantine to the north. In addition Syene had also an administrative and military importance, because customs duties had to be paid and three auxiliary units of 1.500 soldiers were stationed there.